Spherical calcium silicate

Spherical calcium silicate produced through continuous loop reactors solves the problem of unstable particle size and oil absorption properties of existing calcium silicate materials, improves its effectiveness in dental applications, and shows excellent performance in coatings and food fields .

CN119278185APending Publication Date: 2025-01-07EVONIK OPERATIONS GMBH
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
CN202380042947.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-09
Filing Date
2023-05-24
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing calcium silicate materials have problems such as unstable particle size, poor oil absorption and uncertain CaO content in dental applications, which affect their effectiveness and application in oral care.

Method used

Spherical calcium silicate produced by continuous loop reactor process is characterized by a d50 particle size of 1-35μm, oil absorption of 40-130mL/100g, spherical coefficient of greater than 0.80, BET surface area of ​​10-125m2/g and 0.5-20 The percentage of CaO in % combined with calcium hydroxide aging and drying treatment, form calcium silicate particles with spherical morphology and low water absorption.

Benefits of technology

Improves spherical and oil absorption in dental applications, enhances its affinity for enamel and mechanical cleaning capabilities, improves oral care, and exhibits anti-caking and free flow aids in coatings and food fields Excellent properties of the agent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119278185A_ABST
    Figure CN119278185A_ABST
Patent Text Reader

Abstract

A spherical calcium silicate having (i) a d50 median particle size in the range of 1 to 35 [mu] m, (ii) an oil absorption in the range of 40 to 130 mL / 100 g, (iii) a sphericity coefficient (S80) greater than or equal to about 0.80, (iv) a BET surface area between 10 and 125 m2 / g, and (v) a CaO% of 0.5 to 20 wt%. The spherical calcium silicate is produced by (a) continuously feeding a mineral acid and an alkali metal silicate into a loop reaction zone comprising a flow of liquid medium, wherein at least a portion of the mineral acid and the alkali metal silicate react in the liquid medium of the loop reaction zone to form a silica product; (b) continuously recirculating the liquid medium through the loop reaction zone; (c) continuously discharging a portion of the liquid medium comprising the silica product from the loop reaction zone; (d) filtering and washing the liquid medium comprising the silica product; (e) combining the filter cake of step (d) with calcium hydroxide, (f) stirring the combined filter cake of step (e) with calcium hydroxide for 10 min to 180 min (aging step), and (g) drying the solution. The spherical calcium silicate can be used in dentifrice compositions, food mixtures, personal care applications, and liquid coatings.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure generally relates to novel spherical calcium silicates and methods of making and using the same. Background Art

[0002] For many years, synthetic amorphous calcium silicates have been used in food, feed, pharmaceutical and industrial applications. They are produced by reacting previously prepared silicon dioxide or silicate, which is essentially free of sodium sulfate, with a calcium hydroxide slurry at a temperature greater than 60°C (US 1,574,363, US 4,557,916). The reaction results in the formation of calcium silicate particles with high absorption capacity, which can be used in the above-mentioned application areas.

[0003] US 2,204,113 describes a process for producing finely divided calcium silicate, wherein a separate aqueous solution of calcium halide and a separate aqueous solution of a soluble silicate are dripped simultaneously into a reaction vessel at different locations.

[0004] Coating compositions comprising spherical silica or silicates are known from US 2012 / 0216719 A1.

[0005] Calcium silicate is also commonly used in personal care applications (US 7,163,669).

[0006] Calcium silicates are also known to be used in particular in dental compositions, as disclosed in WO 2012 / 078136 A1 and / or WO 2018 / 073062, but without defining the major surface characteristics such as: BET surface area, oil absorption properties or the weight percent amount of CaO present in the particles.

[0007] Silica particles with reduced relative dentin wear (RDA) are disclosed and described in US2020 / 0206107 A1. Such silica particles may have (i) a d50 median particle size greater than or equal to about 6 μm, (ii) a (d90-d10) / d50 ratio in the range of about 1.1 to about 2.4, (iii) an RDA at 20 wt% loading in the range of about 40 to about 200, and (iv) a sphericity coefficient (S) greater than or equal to about 0.9. 80 ). These silica particles have a spherical shape or morphology and can be produced using a continuous loop reactor process.

[0008] Therefore, it would be beneficial to provide a calcium silicate material in oral care that increases soluble calcium levels in saliva and promotes the formation of new hydroxyapatite on the dentin or enamel surface. It may also help that small silica particles designed for tubule sealing have a higher affinity for the dentin surface and are more likely to remain in the mouth after brushing. Since these silicas have a lower surface area than traditional calcium silicate products, they may also provide mechanical cleaning to the tooth surface.

[0009] In coating applications, the calcium silicate materials of the present invention can be used to improve the corrosion resistance of metal substrates. Summary of the invention

[0010] The present summary is provided to introduce in a simplified form a selection of concepts that will be further described in the following detailed description. The present summary is not intended to identify the necessary or essential features of the claimed subject matter. The present summary is also not intended to be used to limit the scope of the claimed subject matter.

[0011] The spherical calcium silicate of the present invention that can be used is disclosed and described herein. According to one aspect of the present invention, such spherical calcium silicate has (i) a d50 median particle size in the range of 1 to 35 μm, (ii) an oil absorption in the range of 40 to 130 mL / 100 g, (iii) a sphericity coefficient (S) greater than or equal to about 0.80. 80 ), (iv) 10-125m 2 / g, and (v) a CaO percentage of 0.5-20 wt%.

[0012] These silica and / or silicate particles have a spherical shape or morphology and can be produced using a continuous loop reactor process.

[0013] Also disclosed herein are dentifrice compositions, cosmetics and coatings containing the spherical calcium silicate of the present invention, and methods of using the spherical calcium silicate and the compositions.

[0014] The foregoing summary of the invention and the following detailed description all provide examples and are illustrative only. Therefore, the foregoing summary of the invention and the following detailed description should not be considered to be restrictive. In addition, features or variations other than those set forth herein may also be provided. For example, certain aspects may be directed to various feature combinations and sub-combinations described in the detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 Continuous loop reactor

[0016] Figure 2 Scanning electron micrograph of the silicate of Example 1A / 1B / 1C.

[0017] Figure 3 Scanning electron micrograph of the silicate of Example 2A / 2B / 2C.

[0018] Figure 4 Scanning electron micrograph of the silicate of Example 3A.

[0019] Figure 5 Scanning electron micrographs of silica / silicates of Examples 4A / 4B / 4C / 4D.

[0020] Figure 6 Scanning electron micrograph of silica / silicate of Examples 5A / 5B / 5C.

[0021] definition

[0022] In order to more clearly define the terms used herein, the following definitions are provided. Unless otherwise stated, the following definitions apply to the present disclosure. If a term is used in the present disclosure but is not specifically defined herein, the definition in the IUPAC Compendium of Chemical Terminology, 2nd Edition (1997) may be applied, as long as the definition does not conflict with any other disclosure or definition applied herein, or does not make any claim to which the definition is applied unclear or infeasible. In the event that any definition or usage provided by any document incorporated herein by reference conflicts with the definition or usage provided herein, the definition or usage provided herein shall prevail.

[0023] In this article, the features of the subject matter are described so that within a particular aspect, a combination of different features can be envisioned. For each aspect and each feature disclosed herein, all combinations that do not adversely affect the design, composition, process or method described herein are considered, and they are interchangeable, whether or not a specific combination is explicitly described. Therefore, unless otherwise explicitly stated, any aspect or feature disclosed herein can be combined to describe an inventive design, composition, process or method that conforms to the present disclosure.

[0024] All publications and patents mentioned herein are incorporated herein by reference for the purpose of describing and disclosing, for example, the constructs and methodologies that are described in the publications, which might be used in connection with the presently described invention. DETAILED DESCRIPTION

[0025] Disclosed herein is a spherical calcium silicate of the present invention characterized by (i) a d50 median particle size in the range of 1 to 35 μm, preferably 1-20 μm, and most preferably 3-15 μm, (ii) an oil absorption in the range of 40 to 130 mL / 100 g, preferably 50-100 mL / 100 g, (iii) a sphericity coefficient (S) greater than or equal to about 0.80, preferably greater than 0.85. 80 ), (iv) 10-125m 2 / g, preferably 30-80m 2 % CaO.

[0026] Also disclosed and described herein are methods of making these spherical silica and / or silicate particles, dentifrice compositions containing the spherical particles, and methods of therapeutically using the spherical particles in dentifrice compositions, cosmetics, and coatings.

[0027] Spherical silicate particles

[0028] In accordance with aspects of the present invention, spherical silicate particles with improved tubule closure may have the following characteristics: (i) a d50 median particle size in the range of 1 to 35 μm, (ii) an oil absorption in the range of 40 to 130 mL / 100 g, (iii) a sphericity coefficient (S) greater than or equal to 0.80. 80 ), (iv) 10-125m 2 / g, and (v) 0.5-20 wt% CaO%. The silicate particles may have any one of the features or properties provided below, and any combination.

[0029] The spherical calcium silicate of the present invention may have a range of 5 to 80 m 2 / g, preferably 10 to 70m 2 / g of CTAB surface area.

[0030] The spherical calcium silicate of the present invention may have a packing density between 0.32 and 0.96 g / ml, preferably between 0.40 and 0.80 g / ml.

[0031] The spherical calcium silicate of the present invention may have a 5% pH between 8.0 and 12.0, preferably between 8.5 and 11.0, more preferably between 9.0 and 10.5.

[0032] The spherical calcium silicate of the present invention may have a Ca:Si weight ratio of 0.015 to 0.60, more preferably 0.04 to 0.30, wherein the amount of Ca reflects the same amount of CaO % as given above and in claim 1 of 0.5-20 wt%, preferably 3-15 wt%.

[0033] The spherical calcium silicate of the present invention can have a relatively low water absorption. For example, the water absorption can be in the range of about 55 to about 115 mL / 100 g, about 65 to about 100 mL / 100 g, or about 70 to about 90 mL / 100 g. Other suitable ranges of water absorption are apparent from this disclosure.

[0034] The spherical calcium silicate of the present invention may be amorphous, may be synthetic, or may be both amorphous and synthetic. In addition, the spherical calcium silicate of the present invention may include precipitated spherical calcium silicate.

[0035] The spherical calcium silicate of the present invention may have a petal-like structure (observed on the surface by an electron microscope).

[0036] Method for producing spherical calcium silicate particles

[0037] The spherical calcium silicate of the present invention can be produced by the following inventive method.

[0038] Generally, the process of the present invention involves (a) continuously feeding an inorganic acid and an alkali metal silicate into a loop reaction zone comprising a stream of a liquid medium, wherein at least a portion of the inorganic acid and the alkali metal silicate react in the liquid medium in the loop reaction zone to form a silica product (e.g., silica and / or silicate particles); (b) continuously recirculating the liquid medium through the loop reaction zone; (c) continuously withdrawing a portion of the liquid medium comprising the silica product from the loop reaction zone; (d) filtering the liquid medium comprising the silica product and washing the filter cake; (e) combining the filter cake of step (d) with calcium hydroxide, (f) stirring the combined filter cake and calcium hydroxide of step (e) for 10 min to 180 min, preferably 60 min to 120 min (aging step), and (g) drying the solution.

[0039] The spherical calcium silicate of the present invention disclosed herein is not limited to any specific synthesis procedure. However, in order to achieve the desired sphericity, the spherical calcium silicate of the present invention can be formed using a continuous loop reactor process of steps (a) to (c). This process and the associated reactor system (which may include a continuous loop of one or more loop reactor pipes) are described in U.S. Patents Nos. 8,945,517 and 8,609,068, which are incorporated herein by reference in their entirety.

[0040] Typically, the feed locations of the inorganic acid and alkali metal silicate into the loop reaction zone are different, and the total feed rate of the acid and silicate is proportional to, and usually equal to, the discharge rate of the liquid medium containing the silica product. All or substantially all of the contents in the loop reaction zone are recycled, for example, at a rate ranging from about 50 vol.% / min (the recycle rate per minute is half the total volume of the contents) to about 1000 vol.% / min (the recycle rate per minute is ten times the total volume of the contents) or from about 75 vol.% / min to about 500 vol.% / min.

[0041] The precipitation device can be configured in a circulation loop, where the reaction slurry can be circulated multiple times before being discharged ( Figure 1). The loop may include fixed piping sections connected together by flexible hose sections. A pump may be placed on one side of the loop to circulate the reaction mixture, and a Silverson in-line mixer may be installed on the other side to provide additional shear to the system and as a convenient location for adding acid. Between the pumps, a static mixer heat exchanger may be installed to provide a means of controlling temperature during silica production. A discharge line located after the acid addition point allows the product to be discharged depending on the rate at which silicate and acid are added. The discharge line may also be equipped with a back pressure valve that enables the system to operate at temperatures greater than 100°C. The product discharge line may be oriented to collect the product into a tank for additional modifications (e.g., pH adjustment), or may be discharged directly into a rotary or pressure filter. Optionally, acid may also be added to the product discharge line to avoid post-synthesis pH adjustment when the product is prepared at a pH greater than 7.0.

[0042] In the case of the present invention, the Silverson inline mixer can be modified to provide high levels of mixing without providing shear. This is achieved by removing the stator screen from the Silverson mixer and operating the unit with just the back plate and normal mixer head. Alternatively, the Silverson mixer can be run with a standard rotor / square hole high shear stator to obtain smaller particle sizes. Particle size can be adjusted in either configuration by changing the Silverson output.

[0043] In process step (d), the filtration can be carried out in a filter press, a rotary vacuum filter, a belt filter or similar solid / liquid separation equipment. Washing of the filter cake can be carried out to reduce salt residues, such as sodium sulfate.

[0044] The combination of the filter cake of step (d) with the calcium hydroxide of step (e) may be carried out in a stirred vessel capable of maintaining the desired temperature between 30 and 100° C. The calcium hydroxide may be a slurry having a calcium hydroxide solids content of 5 to 20%, more preferably 10-18%. The calcium hydroxide may be a slurry in water.

[0045] The stirring in process step (e) may be carried out at a temperature of 30°C to 100°C (aging step), more preferably 60 to 95°C.

[0046] Drying of the calcium silicate (g) can be carried out in a spray dryer or a flash dryer at a temperature sufficient to evaporate the water from the solid.

[0047] The spherical calcium silicate of the present invention can be used in dentifrice compositions, food mixtures, personal care applications and liquid coatings.

[0048] Dentifrice composition

[0049] The spherical calcium silicate of the present invention can be used in any suitable composition and in any suitable final application, such as oral care, personal care, coatings and food fields. Typically, silica and / or silicate particles can be used in oral care applications, such as dentifrice compositions.

[0050] In oral care, calcium can be used for remineralization by increasing soluble calcium levels in saliva and promoting the formation of new hydroxyapatite on the dentin or enamel surface. It may also help that small silica particles designed for tubule sealing have a higher affinity for the dentin surface and are more likely to remain in the mouth after brushing. Since these silicas have a lower surface area than traditional calcium silicate products, they may also provide mechanical cleaning to the tooth surface.

[0051] The dentifrice composition may contain any suitable amount of the spherical calcium silicate of the present invention, such as about 0.5 to about 40 weight %, about 1 to about 35 weight %, about 3 to about 15 weight %, about 3 to about 10 weight % of the spherical calcium silicate of the present invention. These weight percentages are based on the total weight of the dentifrice composition.

[0052] The dentifrice composition may be in any suitable form, such as a liquid, powder or paste. In addition to the silica and / or silicate particles, the dentifrice composition may also contain other ingredients or additives, non-limiting examples of which may include wetting agents, solvents, adhesives, therapeutic agents, chelating agents, thickeners other than the spherical calcium silicate of the present invention, surfactants, abrasives other than the spherical calcium silicate of the present invention, sweeteners, colorants, flavoring agents, preservatives, etc., and any combination thereof.

[0053] Humectants are used to increase the body or "mouth texture" of the dentifrice and to prevent the dentifrice from drying out. Suitable humectants include polyethylene glycols (various molecular weights), propylene glycol, glycerine (glycerol), erythritol, xylitol, sorbitol, mannitol, lactitol and hydrogenated starch hydrolysates, and mixtures thereof. In some formulations, the humectant is present in an amount of about 20 to about 50 weight percent, based on the weight of the dentifrice composition.

[0054] Any suitable loading of solvent may be present in the dentifrice composition, and typically the solvent comprises water. When used, the water is preferably deionized water and free of impurities, and the water may be present in the dentifrice at a loading of 5 to about 70 wt%, or about 5 to about 35 wt%, based on the weight of the dentifrice composition.

[0055] Therapeutic agents may also be used in the compositions of the present invention to provide, for example, prevention and treatment of caries, periodontal disease, and temperature sensitivity. Suitable therapeutic agents may include, but are not limited to, fluoride sources such as sodium fluoride, sodium monofluorophosphate, potassium monofluorophosphate, stannous fluoride, potassium fluoride, sodium fluorosilicate, ammonium fluorosilicate, and the like; condensed phosphates such as tetrasodium pyrophosphate, tetrapotassium pyrophosphate, disodium dihydrogen pyrophosphate, trisodium monohydrogen pyrophosphate; tripolyphosphates, hexametaphosphates, trimetaphosphates, and pyrophosphates; antimicrobial agents such as triclosan, biguanides such as Alexidine, chlorhexidine, and chlorhexidine gluconate; enzymes such as papain, pineapple egg leucase, glucoamylase, amylase, dextranase, mutanase, lipase, pectinase, tannase and protease; quaternary ammonium compounds such as benzalkonium chloride (BZK), benzethonium chloride (BZT), cetylpyridinium chloride (CPC) and domiphene; metal salts such as zinc citrate, zinc chloride and stannous fluoride; bloodroot extract and sanguinarine; volatile oils such as eucalyptol, menthol, thymol and methyl salicylate; amine fluoride; peroxide, etc. The therapeutic agents can be used alone or in combination in the dentifrice formulation and used at any therapeutically safe and effective level or dosage.

[0056] Thickeners can be used in dentifrice compositions to provide a gel-like structure that stabilizes toothpaste to prevent phase separation. Suitable thickeners include silica thickeners; starch; glycerol solutions of starch; gums such as gum karaya (Karayu), gum tragacanth, gum arabic, gum carrageenan, gum acacia, xanthan gum, guar gum, and cellulose gum; magnesium aluminum silicate (Veegum); carrageenan; sodium alginate; agar; pectin; gelatin; cellulosic compounds such as cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxymethyl cellulose, hydroxymethyl carboxypropyl cellulose, methyl cellulose, ethyl cellulose, and sulfated cellulose; (co)polymers of acrylic acid, natural and synthetic clays such as hectorite clay; and mixtures thereof. Typical levels of thickeners or binders are up to about 15% by weight of a toothpaste or dentifrice composition.

[0057] Useful silica thickeners for use in toothpaste compositions include, for example, by way of non-limiting example, amorphous precipitated silicas such as 165 silica. Other non-limiting silica thickeners include 153, 163 and / or 167 and 177 and / or 265 silica products, all available from Evonik.

[0058] Surfactant can be used in the dentifrice composition of the present invention to make the composition more acceptable cosmetically. Surfactant is preferably a decontamination material that imparts decontamination and foaming properties to the composition. Suitable surfactant is an anionic surfactant, a cationic surfactant, a nonionic surfactant, a zwitterionic surfactant, amphoteric surfactant and a betaine surfactant in a safe and effective amount, such as alkali metal or ammonium salts of sodium lauryl sulfate, sodium dodecylbenzene sulfonate, lauroyl sarcosine, myristoyl sarcosine, palmitoyl sarcosine, stearoyl sarcosine and oleoyl sarcosine, polyoxyethylene sorbitan monostearate, isostearate and laurate, sodium lauryl sulfoacetate, N-lauroyl sarcosine, sodium salt, potassium salt and ethanolamine salt of N-lauroyl sarcosine, N-lauroyl, N-myristoyl or N-palmitoyl sarcosine, polyethylene oxide condensates, cocoamidopropyl betaine, lauroamidopropyl betaine, palmityl betaine etc. Sodium lauryl sulfate is a preferred surfactant. Surfactants are typically present in the compositions of the present invention in an amount of about 0.1 to about 15 weight percent, about 0.3 to about 5 weight percent, or about 0.3 to about 2.5 weight percent.

[0059] The disclosed spherical calcium silicate can be used alone as an abrasive in a dentifrice composition, or as an additive or co-abrasive with other abrasive materials discussed herein or known in the art. Therefore, many other conventional types of abrasive additives may be present in the dentifrice composition of the present invention. Other such abrasive particles include, for example, precipitated calcium carbonate (PCC), ground calcium carbonate (GCC), chalk, bentonite, dicalcium phosphate or its dihydrate form, silica gel (itself and any structure), precipitated silica, amorphous precipitated silica (itself and any structure), perlite, titanium dioxide, dicalcium phosphate, calcium pyrophosphate, aluminum oxide, hydrated aluminum oxide, calcined aluminum oxide, aluminum silicate, insoluble sodium metaphosphate, insoluble potassium metaphosphate, insoluble magnesium carbonate, zirconium silicate, granular thermosetting resins and other suitable abrasive materials. Such materials may be introduced into a dentifrice composition to adjust the polishing characteristics of the target formulation.

[0060] Sweeteners can be added to dentifrice compositions (e.g., toothpaste) to impart a pleasant taste to the product. Suitable sweeteners include saccharin (e.g., saccharin sodium, saccharin potassium, or saccharin calcium), sodium cyclamate (e.g., sodium, potassium, or calcium salts), acesulfame potassium, thaumatin, neohesperidin dihydrochalcone, glycyrrhizin, dextrose, levulose, sucrose, mannose, and glucose.

[0061] Colorants may be added to improve the aesthetic appearance of the product. Suitable colorants include, but are not limited to, those approved by appropriate regulatory agencies such as the FDA and those listed in the European Food and Pharmaceutical Directives, and include pigments such as TiO 2 and colorants such as FD&C and D&C dyes.

[0062] Flavoring agents may also be added to the dentifrice composition. Suitable flavoring agents include, but are not limited to, oils of wintergreen, peppermint, spearmint, sassafras and cloves, cinnamon, anethole, menthol, thymol, eugenol, eucalyptol, lemon, orange and other such flavoring compounds that add fruity, spicy, etc. flavors. These flavoring agents typically include mixtures of aldehydes, ketones, esters, phenols, acids and aliphatic, aromatic and other alcohols.

[0063] Preservatives may also be added to the compositions of the present invention to prevent bacterial growth. Suitable preservatives approved for oral compositions, such as methylparaben, propylparaben, and sodium benzoate, may be added in safe and effective amounts.

[0064] Other ingredients may be used in the dentifrice composition, such as desensitizing agents, healing agents, other anticaries agents, chelating / complexing agents, vitamins, amino acids, proteins, other antiplaque / anticarus agents, sunscreens, antibiotics, antienzymes, enzymes, pH control agents, oxidants, antioxidants, and the like.

[0065] How to use

[0066] Any of the spherical calcium silicates and any compositions of the present invention disclosed herein can be used in treatment methods. For example, methods of reducing tooth sensitivity consistent with the present invention may include contacting any of the spherical calcium silicates (or any compositions) disclosed herein with the surface of mammalian teeth. Thus, the spherical calcium silicate (or composition) can be applied to or delivered to the surface of mammalian teeth via brushing or any other suitable technique. Any suitable amount of silicon dioxide and / or silicate particles (or compositions) can be used and for any suitable period of time.

[0067] On the other hand, the method for sealing the dentin tubules in the surface of mammalian teeth in accordance with the present invention may include contacting any spherical calcium silicate (or any composition) disclosed herein with the surface of mammalian teeth. As described above, any suitable amount of spherical calcium silicate (or composition) may be applied or delivered to the surface of mammalian teeth via brushing or any other suitable technique, and for any suitable period of time.

[0068] Sphericity coefficient (S 80) was determined as follows. Scanning electron microscope images were taken on a Zeiss Sigma instrument equipped with a field emission detector. The samples were dispersed in methanol and the methanol slurry was then dried on an aluminum sample holder. Prior to taking the image, the dried sample was sputter coated with platinum to minimize charging.

[0069] An SEM image of a sample of silica and / or silicate particles is magnified 250-2,000 times, which is representative of the sample of silica and / or silicate particles, and is input into photo imaging software, and the outline of each particle is traced (in two dimensions). Particles that are close to each other but not attached to each other should be considered as separate particles for this analysis. The outlined particles are then filled with colorant, and the image is input into particle characterization software (e.g., IMAGE-PRO PLUS available from Media Cybernetics, Inc., Bethesda, Md.) that is capable of determining the perimeter and area of ​​the particles. The sphericity of the particles can then be calculated according to the following equation: Sphericity = (Perimeter) 2 Divide by (4π x area), where perimeter is the software-measured perimeter derived from the contour trajectory of the particle, and where area is the software-measured area within the tracked perimeter of the particle.

[0070] The sphericity calculation was performed for each particle that fit the SEM image perfectly. These values ​​were then sorted by value and the lowest 20% of these values ​​were discarded. The remaining 80% of these values ​​were averaged to obtain the sphericity coefficient (S 80 ). Additional information regarding sphericity can be found in U.S. Patent Nos. 8,945,517 and 8,609,068, which are incorporated herein by reference in their entireties.

[0071] The BET surface areas disclosed herein were determined on a Micromeritics TriStar II 3020 V1.03 using the BET nitrogen adsorption method of Brunaur et al., J. Am. Chem. Soc., 60, 309 (1938), such techniques being well known to those skilled in the art.

[0072] The CTAB surface area disclosed herein is determined by the adsorption of CTAB (hexadecyltrimethylammonium bromide) on the silica surface, the excess portion is separated by centrifugation, and the amount is determined by titrating with sodium lauryl sulfate using a surfactant electrode. Specifically, about 0.5 grams of silica and / or silicate particles are placed in a 250 mL beaker with 100 mL of CTAB solution (5.5 g / L), mixed on an electric stirring plate for 1 hour, and then centrifuged at 10,000 RPM for 30 min. 1 mL of 10% Triton X-100 is added to 5 mL of the clarified supernatant in a 100 mL beaker. The pH is adjusted to 3-3.5 with 0.1 N HCl, and the sample is titrated with 0.01 M sodium lauryl sulfate using a surfactant electrode (Brinkmann SUR1501-DL) to determine the endpoint.

[0073] The d50 median particle size refers to the particle size at which 50% of the sample has a smaller particle size and 50% of the sample has a larger particle size. The median particle size (d50), mean particle size (average) and d95 are determined via laser diffraction method using a Horiba LA 300 instrument. The dried particles are sent to the instrument for analysis.

[0074] For pouring density and packing density, 20 grams of samples are placed in a 250mL graduated cylinder with a flat rubber bottom. Record the initial volume and calculate the pouring density by dividing it by the weight of the sample used. Then the graduated cylinder is placed on a tap density machine and rotated at 60RPM on a cam. The cam is designed to raise and lower the graduated cylinder by a distance of 5.715cm per second once until the sample volume is constant, usually for 15min. Record the final volume and calculate the packing density by dividing it by the weight of the sample used.

[0075] Oil absorption is determined according to the rub-off method described in ASTM D281 using linseed oil (cc of oil absorbed per 100 g of particle). Generally, higher oil absorption levels indicate particles with higher levels of macroporosity, also described as a higher order structure.

[0076] The water absorption value is determined using the Absorptometer "C" torque rheometer from CW Brabender Instruments, Inc. About 1 / 3 cup of the silica sample is transferred to the mixing chamber of the Absorptometer and mixed at 150RPM. Water is then added at a rate of 6mL / min, and the torque required for mixing the powder is recorded. When water is absorbed by the powder, the torque will reach a maximum value due to the powder changing from free flow to a paste. The total volume of water added when the maximum torque is then reached is standardized to the amount of water that 100g of powder can absorb. Since the powder is used as is (not pre-dried), the "moisture-corrected water AbC value" is calculated using the free moisture value of the powder by the following equation.

[0077]

[0078] The Absorptometer is commonly used to determine the oil number of carbon black according to ASTM D 2414 Methods B and C and ASTM D3493.

[0079] The pH values ​​disclosed herein (5% pH) are determined in an aqueous system containing 5 wt% solids in deionized water using a pH meter.

[0080] CaO% (calcium concentration) is determined by the following method. In a platinum crucible, 2.0000g of silica is moistened with a few drops of deionized water. 10ml of perchloric acid (72%) and 10ml of hydrofluoric acid (48-50%) are added in a fume hood and the platinum dish is slowly heated on a stirring plate. When the platinum dish is heated, thick white smoke is produced. The sides of the crucible are then carefully rinsed with boric acid (4%) and also heated to smoke. After cooling, the contents of the crucible are transferred to a 250ml volumetric flask and the crucible is washed with deionized water to ensure quantitative transfer of all remaining contents. The dish is then rinsed with 5ml of hydrochloric acid (36%) and the washings are also added to the volumetric flask. About 200ml of deionized water is added to the volumetric flask and, if the resulting solution is turbid, it is heated on a low temperature hot plate until it becomes clear. After cooling, 2.50ml of scandium internal standard solution is added and the volumetric flask is filled to the mark with deionized water. The metal concentration in the solution is then determined by ICP / OES.

[0081] Sulfate concentration was measured on a LECO SC832 series combustion analyzer from LECO, St. Joseph, Michigan, USA. The sample was placed in a combustion boat and heated to about 1350° C. in an oxygen-rich environment. Carbon and sulfur were released as their respective oxides and measured by IR spectroscopy. The concentration of sulfur or carbon was determined by comparison with a known standard.

[0082] Example

[0083] The present invention is further illustrated by the following examples, which are not to be construed in any way as limiting the scope of the present invention. After reading the description herein, those of ordinary skill in the art may think of various other aspects, modifications and their equivalents without departing from the spirit of the present invention or the scope of the appended claims.

[0084] Continuous loop reactor setup:

[0085] The precipitation device is configured in a circulation loop, wherein the reaction slurry can be circulated multiple times before being discharged ( Figure 1 ). The loop consists of fixed piping sections connected together by flexible hose sections. The inner diameter of the pipe / hose is about 1.5" and the volume is about 45L. A pump is placed on one side of the loop to circulate the reaction mixture, and a Silverson in-line mixer is installed on the other side to provide additional shear to the system and as a convenient location for adding acid. Between the pumps, a static mixer heat exchanger is installed to provide a means of controlling temperature during silica production. A discharge line located after the acid addition point allows product to be discharged depending on the rate at which silicate and acid are added. The discharge line can also be equipped with a back pressure valve that enables the system to operate at temperatures greater than 100°C. The product discharge line can be oriented to collect the product into a tank for additional modifications (such as pH adjustment), or it can be discharged directly into a rotary or pressure filter. Optionally, acid can also be added to the product discharge line to avoid post-synthesis pH adjustment when the product is prepared at a pH greater than 7.0.

[0086] In the case of the present invention, the Silverson in-line mixer can be modified to provide high levels of mixing without providing shear. This is achieved by removing the stator screen from the Silverson mixer and operating the unit with only the back plate and normal mixer head (Example D). Alternatively, the Silverson mixer can be run with a standard rotor / square hole high shear stator to obtain smaller particle sizes (Example C). Particle size can be adjusted in either configuration by changing the Silverson output.

[0087] Initial Setup

[0088] Before the acid and silicate were introduced into the system, precipitated silica, sodium sulfate, sodium silicate and water were added and recirculated at 180 L / min. This step was done to fill the recirculation loop with a typical batch of approximate contents and concentrations to minimize the purge time before the desired product could be collected. This was also to avoid the possibility of gel formation in the reactor, although subsequent experiments have shown that the acid and silicate can be added directly to the loop filled with water without gelling or plugging the system.

[0089] Embodiment 1:

[0090] Add 1.5 kg to the recirculation loop 103, 1.34 kg sodium sulfate, 11.1 L sodium silicate (3.32 MR, 19.5%) and 20 L water and heated to 90°C under 180 L / min recirculation, with Silverson operating at 2320 Hz (1740 RPM), the stator removed, and the shear frequency (5,000-reference 145 patent application). Sodium silicate (3.32 MR, 19.5%) and sulfuric acid (17.1%) are added to the loop simultaneously at a silicate rate of 1.7 L / min and an acid rate sufficient to maintain pH 7.5. If necessary, the acid rate is adjusted accordingly to maintain pH. Acid and silicate are added under these conditions for 40 minutes to purge the unwanted silica from the system, and then the desired material is collected. After 40 minutes, the collection container is emptied and its contents discarded. The silica product is then collected in a container under stirring at 40 RPM while the temperature is maintained at about 80°C. After the desired amount of product was collected, the addition of acid and silicate was stopped and the contents of the loop were filtered to a conductivity of less than 1000 μS / cm.

[0091] Example 1A:

[0092] 30 kg of the silica wet cake (based on dry mass) from Example 1 was combined with 120 L of water and stirred in a stainless steel tank. To this, 8.7 L of a calcium hydroxide slurry having a specific gravity of 1.104 g / mL and approximately 15.6% solids was added to the diluted silica slurry and the mixture was stirred for 60 minutes. After 60 minutes, the entire solution was spray dried to a target moisture of ~5%.

[0093] Example 1B:

[0094] 30 kg of the silica wet cake (based on dry mass) from Example 1 was combined with 120 L of water and stirred in a stainless steel tank. To this, 17.4 L of a calcium hydroxide slurry having a specific gravity of 1.104 g / mL and approximately 15.6% solids was added to the diluted silica slurry and the mixture was stirred for 60 minutes. After 60 minutes, the entire solution was spray dried to a target moisture of ~5%.

[0095] Example 1C:

[0096] 30 kg of the silica wet cake (based on dry mass) from Example 1 was combined with 120 L of water and stirred in a stainless steel tank. To this, 26.1 L of calcium hydroxide slurry with a specific gravity of 1.104 g / mL and about 15.6% solids was added to the diluted silica slurry and the mixture was stirred for 60 minutes. After 60 minutes, the entire solution was spray dried to a target moisture of ~5%.

[0097] Embodiment 2:

[0098] Add 1.5 kg to the recirculation loop 103, 1.34 kg sodium sulfate, 11.1 L sodium silicate (3.32 MR, 19.5%) and 20 L water and heated to 70°C under 180 L / min recirculation, with Silverson operating at 30 Hz (1740 RPM), stator removed, and shear frequency (5,000 - reference same as above). Sodium silicate (3.32 MR, 19.5%) and sulfuric acid (17.1%) are added to the loop simultaneously at a silicate rate of 1.7 L / min and an acid rate sufficient to maintain pH 7.5. If necessary, the acid rate is adjusted accordingly to maintain pH. Acid and silicate are added under these conditions for 40 minutes to purge the unwanted silica from the system, and then the desired material is collected. After 40 minutes, the collection container is emptied and its contents discarded. The silica product is then collected in a container under stirring at 40 RPM while the temperature is maintained at about 80°C. After the desired amount of product has been collected, the addition of acid and silicate is stopped and the contents of the loop are circulated.

[0099] Example 2A:

[0100] 30 kg of the silica wet cake from Example 2 (based on dry mass) was combined with 120 L of water and stirred in a stainless steel tank. To this, 3.7 L of calcium hydroxide slurry with a specific gravity of 1.120 g / mL and about 18.2% solids was added to the diluted silica slurry and the mixture was stirred for 60 minutes. After 60 minutes, the entire solution was spray dried to a target moisture of ~5%.

[0101] Example 2B:

[0102] 30 kg of the silica wet cake from Example 2 (based on dry mass) was combined with 120 L of water and stirred in a stainless steel tank. To this, 7.4 L of a calcium hydroxide slurry having a specific gravity of 1.120 g / mL and approximately 18.2% solids was added to the diluted silica slurry and the mixture was stirred for 60 minutes. After 60 minutes, the entire solution was spray dried to a target moisture of ~5%.

[0103] Example 2C:

[0104] 30 kg of the silica wet cake from Example 2 (based on dry mass) was combined with 120 L of water and stirred in a stainless steel tank. To this, 14.9 L of a calcium hydroxide slurry having a specific gravity of 1.120 g / mL and approximately 18.2% solids was added to the diluted silica slurry and the mixture was stirred for 60 minutes. After 60 minutes, the entire solution was spray dried to a target moisture of ~5%.

[0105] Embodiment 3:

[0106] Add 1.5 kg to the recirculation loop 103, 1.34 kg sodium sulfate, 11.1 L sodium silicate (3.32 MR, 19.5%) and 20 L water and heated to 90°C under 180 L / min recirculation, with Silverson operating at 2320 Hz (1740 RPM), the stator removed, and the shear frequency (5,000-reference 145 patent application). Sodium silicate (3.32 MR, 19.5%) and sulfuric acid (17.1%) are added to the loop simultaneously at a silicate rate of 1.7 L / min and an acid rate sufficient to maintain pH 7.5. If necessary, the acid rate is adjusted accordingly to maintain pH. Acid and silicate are added under these conditions for 40 minutes to purge the unwanted silica from the system, and then the desired material is collected. After 40 minutes, the collection container is emptied and its contents discarded. The silica product is then collected in a container under stirring at 40 RPM while the temperature is maintained at about 80°C. After the desired amount of product was collected, the addition of acid and silicate was stopped and the contents of the loop were filtered to a conductivity of less than 1000 μS / cm.

[0107] Example 3A:

[0108] The filter cake from Example 3 was diluted to 10% solids and pumped to a 400 gallon batch reactor with agitation at 60 RPM. The slurry contained about 45 kg of silica on a dry basis. 11.1 L of a calcium hydroxide slurry having a specific gravity of 1.054 g / mL and about 18.2% solids was added to the silica slurry and the reactor was heated to 95° C. and then aged for 2 hours. After the 2 hour aging time, the batch contents were spray dried to a target moisture of 5%.

[0109] The chemical and physical data are shown in Tables 1 and 2.

[0110] Table 1: Chemical data

[0111]

[0112] Table 2: Physical data

[0113]

[0114] Embodiment 4:

[0115] Comparative Example 4A:

[0116] Add 1.5 kg to the recirculation loop 103, 1.34 kg sodium sulfate, 11.1 L sodium silicate (3.32 MR, 19.5%) and 20 L water were heated to 83°C under 180 L / min recirculation, with the stator installed in the Silverson. Sodium silicate (3.32 MR, 13.3%) and sulfuric acid (11.4%) were added to the loop simultaneously at a silicate rate of 6.4 L / min and an acid rate sufficient to maintain pH 7.5. The acid rate was adjusted accordingly to maintain pH if necessary. Acid and silicate were added under these conditions for 40 minutes to purge the unwanted silica from the system, and then the desired material was collected. After 40 minutes, the collection container was emptied and its contents discarded. The silica product was then collected in a container under stirring at 40 RPM while the temperature was maintained at about 80°C. After the desired amount of product was collected, the addition of acid and silicate was stopped and the contents of the loop were filtered to a conductivity of less than 1000 μS / cm and then spray dried to a target moisture of 5%.

[0117] Comparative Example 4B:

[0118] 200 g of Comparative Example 4A was slurried in water at 10% concentration and heated to 60° C. (enough to keep the silica from settling) with overhead stirring at 300 RPM. 64 ml of an aqueous calcium hydroxide slurry (17.5% solids, 1.12 g / ml) was added to the silica slurry and the reaction mixture was aged for 45 minutes with stirring at 300 RPM. After 45 minutes, the reaction mixture was filtered and oven dried at 105° C. overnight.

[0119] Comparative Example 4C:

[0120] 200 g of Comparative Example 4A was slurried in water at 10% concentration and heated to 60° C. (enough to keep the silica from settling) with 300 RPM overhead stirring. 86 ml of an aqueous calcium hydroxide slurry (17.5% solids, 1.12 g / ml) was added to the silica slurry and the reaction mixture was aged for 45 minutes with 300 RPM stirring. After 45 minutes, the reaction mixture was filtered and oven dried at 105° C. overnight.

[0121] Comparative Example 4D:

[0122] 200 g of Comparative Example 4A was slurried in water at 10% concentration and heated to 60° C. (enough to keep the silica from settling) with 300 RPM overhead stirring. 110 ml of an aqueous calcium hydroxide slurry (17.5% solids, 1.12 g / ml) was added to the silica slurry and the reaction mixture was aged for 45 minutes with 300 RPM stirring. After 45 minutes, the reaction mixture was filtered and oven dried at 105° C. overnight.

[0123] Embodiment 5:

[0124] Comparative Example 5A:

[0125] Add 1.5 kg to the recirculation loop 103, 1.34 kg sodium sulfate, 11.1 L sodium silicate (3.32 MR, 19.5%) and 20 L water and heated to 90°C under 180 L / min recirculation, with Silverson operating at 2320 Hz (1740 RPM), the stator removed, and the shear frequency (5,000-reference 145 patent application). Sodium silicate (3.32 MR, 19.5%) and sulfuric acid (17.1%) are added to the loop simultaneously at a silicate rate of 1.7 L / min and an acid rate sufficient to maintain pH 7.5. If necessary, the acid rate is adjusted accordingly to maintain pH. Acid and silicate are added under these conditions for 40 minutes to purge the unwanted silica from the system, and then the desired material is collected. After 40 minutes, the collection container is emptied and its contents discarded. The silica product is then collected in a container under stirring at 40 RPM while the temperature is maintained at about 80°C. After the desired amount of product was collected, the addition of acid and silicate was stopped and the contents of the loop were filtered to a conductivity of less than 1000 μS / cm and then spray dried to a target moisture of 5%.

[0126] Example 5B:

[0127] 200 g of Comparative Example 5A was slurried in water at 10% concentration and heated to 60° C. (enough to keep the silica from settling) with 300 RPM overhead stirring. 64 ml of an aqueous calcium hydroxide slurry (17.5% solids, 1.12 g / ml) was added to the silica slurry and the reaction mixture was aged for 2.5 hours with 300 RPM stirring. After 45 minutes, the reaction mixture was filtered and oven dried at 105° C. overnight.

[0128] Example 5C:

[0129] 200 g of Comparative Example 5A was slurried in water at 10% concentration and heated to 60° C. (enough to keep the silica from settling) with overhead stirring at 300 RPM. 110 ml of an aqueous calcium hydroxide slurry (17.5% solids, 1.12 g / ml) was added to the silica slurry and the reaction mixture was aged for 2.5 hours with stirring at 300 RPM. After 45 minutes, the reaction mixture was filtered and oven dried at 105° C. overnight.

[0130] The chemical and physical data are shown in Table 3.

[0131] Table 3

[0132]

[0133] Embodiment 6:

[0134] Add 1.5 kg to the recirculation loop 103, 1.34 kg sodium sulfate, 11.1 L sodium silicate (3.32 MR, 19.5%) and 20 L water and heated to 83°C under 180 L / min recirculation, where the stator is installed in Silverson. Sodium silicate (3.32 MR, 13.3%) and sulfuric acid (11.4%) are added to the loop simultaneously at a silicate rate of 6.4 L / min and an acid rate sufficient to maintain pH 7.5. If necessary, the acid rate is adjusted accordingly to maintain pH. Acid and silicate are added under these conditions for 40 minutes to purge the unwanted silica from the system, and then the desired material is collected. After 40 minutes, the collection container is emptied and its contents are discarded. The silica product is then collected in a container under stirring at 40 RPM while maintaining the temperature at about 80°C. After the desired amount of product is collected, the addition of acid and silicate is stopped and the contents of the loop are filtered to a conductivity of less than 1000 μS / cm.

[0135] Example 6A:

[0136] 30 kg of the silica wet cake from Example 6 (based on dry mass) was combined with 120 L of water and stirred in a stainless steel tank. To this, a calcium hydroxide slurry containing 1.5 kg of calcium hydroxide (based on dry matter) was added to the diluted silica slurry and the mixture was stirred for 60 minutes at ambient temperature. After 60 minutes, the entire solution was spray dried to a target moisture of ~5%.

[0137] Example 6B:

[0138] 30 kg of the silica wet cake (based on dry mass) from Example 6 was combined with 120 L of water and stirred in a stainless steel tank. To this, a calcium hydroxide slurry containing 4.5 kg of calcium hydroxide (based on dry matter) was added to the diluted silica slurry and the mixture was stirred for 60 minutes at ambient temperature. After 60 minutes, the entire solution was spray dried to a target moisture of ~5%.

[0139] Embodiment 7:

[0140] Add 1.5 kg to the recirculation loop 103, 1.34 kg sodium sulfate, 11.1 L sodium silicate (3.32 MR, 19.5%) and 20 L water and heated to 70°C under 180 L / min recirculation, where the stator is installed in Silverson. Sodium silicate (3.32 MR, 13.3%) and sulfuric acid (11.4%) are added to the loop simultaneously at a silicate rate of 6.4 L / min and an acid rate sufficient to maintain pH 7.5. If necessary, the acid rate is adjusted accordingly to maintain pH. Acid and silicate are added under these conditions for 40 minutes to purge the unwanted silica from the system, and then the desired material is collected. After 40 minutes, the collection container is emptied and its contents are discarded. The silica product is then collected in a container under stirring at 40 RPM while maintaining the temperature at about 80°C. After the desired amount of product is collected, the addition of acid and silicate is stopped and the contents of the loop are filtered to a conductivity of less than 1000 μS / cm.

[0141] Example 7A:

[0142] 30 kg of the silica wet cake (based on dry mass) from Example 6 was combined with 120 L of water and stirred in a stainless steel tank. To this, a calcium hydroxide slurry containing 4.5 kg of calcium hydroxide (based on dry matter) was added to the diluted silica slurry and the mixture was stirred for 60 minutes at ambient temperature. After 60 minutes, the entire solution was spray dried to a target moisture of ~5%.

[0143] Example 7B:

[0144] 30 kg of the silica wet cake from Example 6 (based on dry mass) was combined with 120 L of water and stirred in a stainless steel tank. To this, a calcium hydroxide slurry containing 6.0 kg of calcium hydroxide (based on dry matter) was added to the diluted silica slurry and the mixture was stirred for 60 minutes at ambient temperature. After 60 minutes, the entire solution was spray dried to a target moisture of ~5%.

[0145] Embodiment 8:

[0146] Add 1.5 kg to the recirculation loop 103, 1.34 kg sodium sulfate, 11.1 L sodium silicate (3.32 MR, 19.5%) and 20 L water and heated to 83°C under 180 L / min recirculation, where the stator is installed in Silverson. Sodium silicate (3.32 MR, 13.3%) and sulfuric acid (11.4%) are added to the loop simultaneously at a silicate rate of 6.4 L / min and an acid rate sufficient to maintain pH 7.5. If necessary, the acid rate is adjusted accordingly to maintain pH. Acid and silicate are added under these conditions for 40 minutes to purge the unwanted silica from the system, and then the desired material is collected. After 40 minutes, the collection container is emptied and its contents are discarded. The silica product is then collected in a container under stirring at 40 RPM while maintaining the temperature at about 80°C. After the desired amount of product is collected, the addition of acid and silicate is stopped and the contents of the loop are filtered to a conductivity of less than 1000 μS / cm.

[0147] Example 8A:

[0148] The filter cake from Example 8 was diluted to 10% solids and pumped to a 400 gallon batch reactor with agitation at 60 RPM. The slurry contained about 45 kg of silica on a dry basis. 39.1 L of a calcium hydroxide slurry having a specific gravity of 1.104 g / mL and about 15.6% solids was added to the silica slurry and the reactor was heated to 95° C. and then aged for 2 hours. After the 2 hour aging time, the batch contents were spray dried to a target moisture of 5%.

[0149] The chemical and physical data are shown in Tables 4 and 5.

[0150] Table 4: Chemical data

[0151]

[0152] Table 5: Physical data

[0153]

[0154] Figure 2-6 The SEM images in show the spherical particle morphology of calcium silicate. When observing the surface of the calcium silicate material of the present invention, a petal-like structure is sometimes observed. The petal-like structure is described as a rose-like structure in US 6287530, Section 5, Line 56, which can be observed on the surface by an electron microscope. Without being bound by a particular theory, it is believed that the petal-like structure can lead to a higher level of accessible calcium, which may be beneficial for applications in oral care, cosmetics, coatings and food fields.

[0155] Embodiment 9: Toothpaste preparations

[0156] In oral care, calcium can be used for remineralization by increasing soluble calcium levels in saliva and promoting the formation of new hydroxyapatite on the dentin or enamel surface. It may also help small silica particles designed for tubule closure have a higher affinity for the dentin surface and are more likely to remain in the mouth after brushing. Since these silicas have a lower surface area than traditional calcium silicate products, they can also provide mechanical cleaning for the tooth surface. PCR and RDA testing was performed at the Indiana University School of Dentistry.

[0157] The toothpaste formulations and data are shown in Table 6 below.

[0158] Relative dentin wear (RDA)

[0159] The RDA values ​​of the dentifrice compositions of Examples DC1-DC14 containing the silica of the present invention were determined according to the method set forth in Hefferen, Journal of Dental Res., July-August 1976, 55(4), pp. 563-573 and described in U.S. Pat. Nos. 4,340,583, 4,420,312, and 4,421,527 to Wason, the contents of which are incorporated herein by reference in their entirety.

[0160] Film Cleaning Rate (“PCR”)

[0161] The cleaning properties of a dentifrice composition are often expressed as a Pellicle Cleaning Ratio ("PCR") value. The PCR test measures the ability of a dentifrice composition to remove pellicle from teeth under fixed brushing conditions. The PCR test is described in "In Vitro Removal of Stain with Dentifrice" by GK Stookey et al., J. Dental Res., 61, 12-36-9, 1982. Both PCR and RDA results vary depending on the nature and concentration of the dentifrice composition components. PCR and RDA values ​​are unitless.

[0162] Table 6

[0163]

[0164] Embodiment 10: Food mixture

[0165] Calcium silicates are also used as anti-caking and free-flowing aids in food applications. They are typically added to spices and / or food mixtures at levels in the range of 1-2% to improve flow and handling properties during food preparation. A study was conducted to show the efficacy of these materials as anti-caking and free-flowing aids in table salt. Table salt was treated with 1.5% (double checked) of each prototype calcium silicate and mixed thoroughly. The salt samples were then exposed to moisture (room or added water) and tested for fluidity. It was found that the flow characteristics of the salt control without calcium silicate were significantly worse than the salt samples containing calcium silicate of the present invention. The data are shown in Table 7 below.

[0166] Angle of repose and compressibility testing were performed on a Model PT-S Powder Tester from Hosokawa Micron Corporation, Summit, NJ, according to the instructions provided with the instrument.Wetting salts and wetting salts containing 2 weight percent of the calcium silicate of the present invention were evaluated.

[0167] Angle of repose tests were performed and a lower slope was observed for the salt containing calcium silicate. The lower angle of repose values ​​for the samples are due to a reduction in particle to particle cohesion, which indicates improved flowability.

[0168] The compressibility value is determined by the ratio of the aerated bulk density to the packed bulk density. The lower compressibility values ​​are due to the salt samples containing calcium silicate, which reduces the cohesion between particles, allowing the salt to fill a given volume more efficiently. It was found that all samples containing calcium silicate of the present invention resulted in lower compressibility values ​​and improved flowability.

[0169] Table 7

[0170] Example Angle of repose (°) Compressibility (%) Control salt 48 17.3 6A 43 11.8 6B 44 12.8 7A 45 11.9 8A 42 12.3

[0171] Embodiment 11: Personal Care Applications

[0172] Calcium silicate is also commonly used in personal care applications (US7,163,669). Because these calcium silicates have a spherical shape, they can be used for skin sensation while also providing the ability to neutralize acidic odors. Previous work has shown that the ability to absorb acidic odors from sebum is an important function in deodorants and antiperspirants. The acid neutralization ability of the sample is evaluated by HCl titration. The calcium silicate to be tested is slurried with 5 weight % and mixed with 300RPM in a ZetaProbe acoustic zeta potential meter from Colloidal Dynamics. The instrument is equipped with an automatic pipette system that allows accurate addition of liquid solutions. 1.0M HCl is added at 0.25ml / min until the pH is stabilized at 4.0. The acid volume required to reduce the pH to 4.0 is directly related to the neutralization ability of the calcium silicate prototype. The acid neutralization ability is shown in Table 8 below.

[0173] Table 8

[0174] Example Volume of 1.0M HCl added (ml) 6A 9.67 6B 36.4 7A 35.6 7B 52.4 8A 28.6

[0175] Embodiment 12: Preparation of liquid coatings

[0176] Preparation of solvent-based formulations (Examples 12A-12B)

[0177] Formulation Examples 12A and 12B were prepared by mixing the ingredients of the components together at ambient room temperature in the order listed in Table 9. 2.5 mm ceramic grinding media was then added to the container (mass ratio of media to total formulation was 1:1). The formulation was milled on a LAU disperser for 2 h to obtain a Hegman score of 6 (25.4 microns). The grinding media was separated using a 226 micron mesh filter.

[0178] Table 9. Solvent-based high solid silicone formulations*

[0179] Join Order Components Example 12A Example 12B Silikophen P80X Silicone resin 43.7 43.7 Xylene Solvents 23.8 23.8 Butyl glycol acetate Solvents 1.7 1.7 Isobutanol Solvents 0.3 0.3 TEGO Dispers 670 Dispersants 0.8 0.8 TEGO Airex 900 Defoaming agent 0.4 0.4 Aerosil 200 Silica Thixotropic Rubber 0.6 0.6 Bentone 38 Clay Thickener 0.3 0.3 Heucophos ZPO ACP (zinc phosphate) 3.9 --- Example 6B ACP (Calcium Silicate) --- 3.9 Ti Pure R 706 <![CDATA[TiO 2 ]]> 13.2 13.2 Mica Suzorite 325S Mica 11.6 11.6 total 100 100 Solid percentage (%w / w) 65 65

[0180] *Formulation prepared using 3.9% corrosion inhibitor

[0181] ACP: Anti-corrosion Pigment

[0182] Preparation of aqueous formulations (Examples 12C-12D)

[0183] Formulation Examples 12C and 12D were similarly prepared by first mixing the ingredients of package A together (except the epoxy resin and thickener) at ambient room temperature in the order listed in Table 10. Grind with a cowl blade on a Dispermat for at least 30 minutes to obtain a Hegman score of 6 (25.4 microns). Then add the epoxy resin and thickener and mix for an additional 10 minutes. Prepare Formulation B package by mixing the curing agent and solvent before coating application.

[0184] Table 10. Waterborne 2k Epoxy Primer Formulation**

[0185] Join Order Components Example 12C Example 12D Package A Deionized water Solvents 10.9 10.9 TEGO Dispers 757W Dispersants 1.2 1.2 Surfynol DF 75 Defoaming agent 0.4 0.4 Surfynol 420 Wetting Agents 0.4 0.4 Red Iron Oxide pigment 6.4 6.4 Zeeospheres G 400 Ceramic microspheres 5.5 5.5 Sparwite barite Barium sulfate 5.5 5.5 Wollastocoat 10ES Calcium silicate chain 5.5 5.5 Halox SW 111 ACP (Zinc-free Corrosion Inhibitor) 8.5 --- Example 6B ACP (Calcium Silicate) --- 8.5 Mica 325 Mica 0.8 0.8 Ancarez AR555 Epoxy resin 36.5 36.5 Rheolate 310 (15% aqueous solution) Thickener 2.8 2.8 Package B Anquamine 419 Curing agent 10.0 10.0 Propylene glycol methyl ether Solvents 2.9 2.9 Deionized water Solvents 2.7 2.7 total 100 100 Solid percentage (%w / w) 60 60

[0186] *Formulation prepared using 8.5% corrosion inhibitor

[0187] ACP: Anti-corrosion Pigment

[0188] Coating Application

[0189] The solvent-based coating was applied to 4×6 cold rolled steel panels at 3 mils wet film thickness using a drawdown bar and allowed to flash overnight in ventilation conditions. The samples were baked at 250C for 30 minutes.

[0190] The waterborne coating was applied to 4×6 cold rolled steel panels at 6 mils wet film thickness using a drawdown bar and allowed to cure for 7 days at ambient conditions.

[0191] Testing of Cured Coatings

[0192] Solvent-based and water-based coatings were evaluated in a similar manner. Panels were scored using a box cutter blade in accordance with ASTM D1654. Exposed metal edges and backs of panels were covered with vinyl tape.

[0193] Solvent-based samples were subjected to 300h salt spray corrosion test, while water-based samples were subjected to 1000h salt spray corrosion test. After reaching 300h (for solvent-based) and 1000h (for water-based samples), the panel was removed and the surface was wiped dry. The panel was scratched with a metal scraper, and 8 scribe creep measurements were performed evenly along the scribe according to ASTM D1654. The average scribe creep is the average of 8 measurements.

[0194] Table 11 shows the results of the scribe creep measurements.

[0195] Table 11

[0196]

[0197] The inventive examples (12B and 12D) exhibit comparable anti-corrosion performance to current commercial benchmark anti-corrosion pigments (12A and 12C).

[0198] Additionally, embodiments of the present invention have environmental benefits due to the calcium silicate compared to using traditional additive phosphates.

Claims

1. A spherical calcium silicate having: (i) a d50 median particle size in the range of 1 to 35 μm, preferably 1-20 μm, most preferably 3-15 μm, (ii) an oil absorption in the range of 40 to 130 mL / 100 g, preferably 50-100 mL / 100 g, (iii) a sphericity coefficient (S) greater than or equal to about 0.80, preferably greater than 0.85 80 ), (iv) 10-125m 2 / g, preferably 30-80m 2 / g between BET surface areas, It is characterized in that The spherical calcium silicate comprises (v) 0.5-20 wt. %, preferably 3-15 wt. % CaO.

2. Spherical calcium silicate according to claim 1, wherein the CTAB surface area is 5 to 80 m 2 / g, preferably 10 to 70m 2 / g.

3. spherical calcium silicate according to claim 1, wherein packing density is between 0.32 to 0.96 g / mL, preferably between 0.40 to 0.80 g / mL.

4. The spherical calcium silicate according to claim 1, wherein the 5% pH is between 8.0 and 12.0, preferably between 8.5 and 11.0, more preferably between 9.0 and 10.

5.

5. Spherical calcium silicate according to claim 1, wherein the water absorption is in the range of 55 to 115 mL / 100 g, preferably 65 to 100 mL / 100 g, more preferably 70 to 90 mL / 100 g.

6. Spherical calcium silicate according to claim 1, wherein the Ca:Si weight ratio is between 0.015 and 0.600, preferably between 0.04 and 0.

30.

7. A method for producing spherical calcium silicate according to claims 1 to 6, which involves (a) continuously feeding a mineral acid and an alkali metal silicate into a loop reaction zone comprising a liquid medium stream, wherein at least a portion of the mineral acid and the alkali metal silicate react in the liquid medium of the loop reaction zone to form a silica product; (b) continuously recirculating the liquid medium through the loop reaction zone; (c) continuously discharging a portion of the liquid medium containing the silica product from the loop reaction zone; (d) filtering and washing the liquid medium containing the silica product; (e) combining the filter cake of step (d) with calcium hydroxide, (f) stirring the combined filter cake of step (e) and calcium hydroxide for 10 min to 180 min, preferably 60 min to 120 min (aging step), and (g) drying the solution.

8. The method for producing spherical calcium silicate according to claim 7, wherein the feeding positions of the inorganic acid and the alkali metal silicate into the loop reaction zone are different.

9. The method for producing spherical calcium silicate according to claim 7, wherein the total feed rate of the acid and the silicate in step (a) is proportional to or equal to the discharge rate of the liquid medium containing the silicon dioxide product (c).

10. The method for producing spherical calcium silicate according to claim 7, wherein in step (b), all or substantially all contents in the loop reaction zone are recycled at a rate in the range of 50 vol.% / min to 1000 vol.% / min.

11. Use of spherical calcium silicate according to claims 1 to 6 in dentifrice compositions, food mixtures, personal care applications and liquid coatings.

12. A dentifrice composition comprising the spherical calcium silicate according to any one of claims 1 to 6.

13. A coating composition comprising the spherical calcium silicate according to any one of claims 1 to 6.

14. A food composition comprising the spherical calcium silicate according to any one of claims 1 to 6.

15. A cosmetic composition comprising the spherical calcium silicate according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Siliceous alkalline-earth product and process of making the same

    US1574363A

  • Coating compositions comprising spheroid silica or silicate

    US20120216719A1

  • Spherical silica particle size for RDA control

    US20200206107A1

  • Calcium silicate and method of preparing the same

    US2204113A

  • High fluoride compatibility dentifrice abrasives and compositions

    US4340583A